Problem Based Learning (PBL) Model with Technological, Pedagogical, and Content Knowledge (TPACK) Approach (International Journal of Education in Mathematics, Science and Technology, 2022)
This research aims to determine whether there is an influence of applying the Problem Based Learning (PBL) Model with the Technological, Pedagogical, and Content Knowledge (TPACK) Approach on the historical learning outcomes of high school students of Sultan Iskandar Muda Medan. This study uses a quasi-experiment research method. The population in this study involves all students of class XI of High School (SMA) Sultan Iskandar Muda Medan, with a sample of class XI of Social Sciences (IPS) 1 as an experiment class and class XI of Social Sciences (IPS) 3 as a control class selected by simple random sampling method. The experiment class is taught with the PBL Model with the TPACK Approach, while the control class is taught with the Discovery Learning Model. The research instrument used is in the form of test questions totaling 25 multiple choice questions that have been declared valid. In this study, two stages of the test were given, namely pretest and posttest, in the form of multiple-choice questions that have been declared valid. The pretest is given to both sample classes to determine the student's initial ability before being given treatment, while the posttest is given to both sample classes to determine the final ability of learners after treatment. Based on posttest data, the experiment class obtained an average score of 80.3 and an average score in the control class of 68.4. The data proved to be a normal and homogeneous distribution through statistical test analysis, so a hypothesis test was carried out, namely a one-party t-test that showed a significance level of α = 0.05. Thus, Ho was rejected, and Ha was accepted, meaning that there was an influence of the PBL Model with the TPACK Approach on the historical learning outcomes of the high school students.
Keywords: Problem Based Learning; PBL; Technological; Pedagogical; and Content Knowledge; TPACK; Discovery Learning Model; Historical learning outcomes